Pengaruh Sistem Aerasi Dan Pemangkasan Akar Terhadap Produksi Bayam Merah (Amaranthus Tricolor L.) Pada Hidroponik Rakit Apung - Virha, Fikha Anggraeni; Bastamansyah, Bastamansyah; Bayfurqon, Fawzy Muhammad (Universitas Medan Area, 2020)
Red spinach is a leaf vegetable that has uniqueness and good properties for health. This study aims to study and obtain root pruning that gives the best results to the production of redspinach (Amaranthus tricolor L.) in hydroponic technology floating system at each administration of the same aeration system. This research was conducted in October -November 2020 at Screen House located at Perum Trias Estate Jl. Euphorbia 3, Wanasari Village, Kec, Cibitung, BekasiDistrict. The design used is RandomIzed Group Design (RAK) with two factors, aeration system as the first factor consisting of three levels, namely, styrofoam touch solution (a0); aerator (a1); styrofoam with support (a2), and root pruning as the second factor consisting of two levels, namely, without root pruning (p0) and root pruning 50% (p1) of the root length at the age of 2 MST. The observed parameters include the height of the plant, the number of leaves of the plant, the area of the leaves of the plant and the fresh weight of the plant. Data of observation results in the test using F test 5% which if the results are significant followed by dmrt further test level of 5%. The results showed that there is an interaction between the aeration system and root pruning to the number of leaves of plants aged 4 MST